Syncretism of coaching science in ancient Greece and modern times - Stefanovic, D.; Ioannidis, T.; Kariofu, M. (Serbian Journal of Sports Sciences, 2008)
The aim of this theoretical scientific study was to investigate thoroughly into the phenomenon of sports training as comprehended both in ancient Greece and in modern times by establishing objective truth. Research into relevant information revealed levels of syncretism between how ancient Greeks understood the phenomenon of sport training and contemporary coaching theory/science. The science of sport training is included in the scientific system of sports, and, like other scientific disciplines, has its structural elements, i.e., its general information, function, basic concepts, methodology, and relationship with practice. There are several systems in sports: the system of preparing the athlete, the human-machine system, the training system, the system of performance in competition, etc. The application of coaching science/theory in practice is essential for the process of coach education. Just as in modern times, sport training in ancient Greece included specialist coaches, experts from sport medicine, scientists and others. In ancient times there were collective preparations for the Olympic games, and nowadays there are simulation camps that are included in the preparations for major competitions. It was in ancient Greece that there appeared the first training aimed exclusively at sport competitions. Ever since the classical times, the structure of training has remained practically the same. Ancient Greeks knew of the basic principles of training. There used to be sketches of the training where now computer technology and video equipment are used for analysis of training and competition. Music has been used in training and competing as a stimulus for achieving success/good results in the chosen sport activity. Both periods have paid great attention to the area of recovery. Considerations of coaching science have always corresponded to the existing technology and the levels of knowledge. Using terminology, selecting athletes, categorizing competitors, preparing comprehensively, using optimal load in training, being aware of periodization (microcycles), diet and other considerations form a strong link between knowledge on sport training from the two sport cultures of different eras. The practical aspect of this theoretical research lies in systematizing and broadening the insight into science/theory of sport training, which is fundamental for transfer of knowledge into practice. Such stimulation of creative thinking is vital for the development of scientific thought in the area of training and coaching.